Constitutional Cultures : On the Concept and Representation of Constitutions in the Atlantic World. - Hensel, Silke (Cambridge Scholars Pub., 2012)
Written constitutions are an important attribute of nation states and have become a global phenomenon over the past 200 years. The process began with the revolutions in the Atlantic World, from where it spread to other regions. The present volume looks into the complex of constitutions, the fundamental values conveyed by the constitutional texts, the building and functioning of new constitutional bodies and their symbolic representation. All the authors work on the assumption that in order to ...